AB0166 IMMUNOGLOBULIN G DERIVED FROM PATIENTS WITH SYSTEMIC SCLEROSIS IMPRINTS A PRO-INFLAMMATORY AND PRO-FIBROTIC PHENOTYPE IN MONOCYTE-LIKE THP-1 CELLS. (2nd June 2020) - Dalmann, A.; Murthy, S.; Wannick, M.; Eleftheriadis, G.; Müller, A.; Zillikens, D.; Busch, H.; Sadik, C.; Riemekasten, G.
Abstract : Background: Regulatory IgG autoantibodies directed against diverse G protein-coupled receptors (GPCR), i.e. antibodies with agonistic or antagonistic activity are abundant in human serum. The serum titers of autoantibodies targeting angiotensin II receptor 1 (AT1 ) and endothelin receptor A (ETA ) are specifically altered in autoimmune diseases such as systemic sclerosis (SSc). Disease-promoting mechanisms regulated by anti-AT1 and anti-ETA IgG are still elusive, but induction of pro-inflammatory and pro-fibrotic chemokines (CXCL8, CCL18) has been suggested to be one of them. Objectives: To determine the cytokine and phospho-kinase profiles induced in monocyte-like cells by IgG derived from SSc patients (SSc-IgG) enriched with anti-AT1 and anti-ETA antibodies in comparison to IgG derived from healthy donors (IgG-HD). Methods: A monocyte-like cell line (THP-1) was cultured in vitro and stimulated with IgG (1 mg/ml) derived from SSc patients or HD in the presence of various inhibitors/blockers for 24h. Then, supernatants were analyzed by a human cytokine/chemokine array. Data were analyzed using bio-mathematical tools such as generalized t-test including the robust regression method from R/Bioconductor package LIMMA. In addition, THP-1 cells were cultured in vitro and stimulated with IgG (1 mg/ml) derived from SSc patients or HD for up to 30 minutes. Thereafter, cell lysates were assayed for the kinome employing a human phospho-kinase array. To validate potential effects of transcription factor inhibition, release of CXCL8 and CCL18 into the supernatant was measured by Elisa. Results: In general, SSc-IgG induced the release of most cytokines by THP-1 cells more pronouncedly than HD-IgG. The bio-mathematical analysis suggested that stimuli, responsible for the shift of the THP-1 cell cytokine profile, are more abundant in SSc-IgG than in HD-IgG. Based upon these findings a gene set enrichment analysis for transcription factors yielded the transcription factors NF-κB, AP-1, and PRDM1 (Blimp-1) as putative major regulatory hubs for the response of THP-1 cells to SSc-IgG. Further, SSc-IgG altered the phosphorylation status of several proteins, indicative of an involvement of MAPK and/or JAK/STAT pathways. Interestingly, a role for AP-1 was also proposed by the inhibition of CXCL8 and CCL18 release following pretreatment of THP-1 cells with an AP-1 blocker. Conclusion: Herein, we demonstrate that IgG of SSc patients, enriched with anti-AT1 and anti-ETA autoantibodies drives THP-1 cells towards a general pro-inflammatory and pro-fibrotic phenotype, which is reflected by broad changes in the secretome and kinome of these cells. Furthermore, our results highlight AP-1 as critical regulator of gene transcription of CXCL8 and CCL18 in a monocyte-like cell line. References: [1]Cabral-Marques O, Marques A, Giil LM, De Vito R, Rademacher J, Günther J, Lange T, Humrich JY, Klapa S, Schinke S, et al. GPCR-specific autoantibody signatures are associated with physiological and pathological immune homeostasis. Nat Commun (2018) 9 :5224. doi:10.1038/s41467-018-07598-9 [2]Günther J, Kill A, Becker MO, Heidecke H, Rademacher J, Siegert E, Radi M, Burmester G-R, Dragun D, Riemekasten G. Angiotensin receptor type 1 and endothelin receptor type A on immune cells mediate migration and the expression of IL-8 and CCL18 when stimulated by autoantibodies from systemic sclerosis patients. Arthritis Res Ther (2014) 16 :R65. doi:10.1186/ar4503 Disclosure of Interests: Anja Dalmann: None declared, Sripriya Murthy: None declared, Melanie Wannick: None declared, Georgios Eleftheriadis: None declared, Antje Müller: None declared, Detlef Zillikens: None declared, Hauke Busch: None declared, Christian Sadik: None declared, Gabriela Riemekasten Consultant of: Cell Trend GmbH, Janssen, Actelion, Boehringer Ingelheim, Speakers bureau: Actelion, Novartis, Janssen, Roche, GlaxoSmithKline, Boehringer Ingelheim, Pfizer